Subcontractors Selection of Building Construction Project Using Analytical Hierarchy Process (AHP) and Technique for Others Reference by Similarity (TOPSIS) Methods - Caesarani Gloria Putri; Dewi Nusraningrum (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This research aims to identify the most important qualification criteria for selecting subcontractors in the construction supply chain. Design/Methods/Approach: The criteria calculations were analyzed based on the Analytical Hierarchy Process (AHP) method applied to obtain the weight of the subcontractor selection criteria. The Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) method was used to evaluate the different subcontractors against 22 sub-criteria indicators. The research sample is the Project Manager and Commercial Manager, who are the decision-makers in selecting subcontractors. Findings: Quality, Health, Safety, and Environment (HSE) and Price are the highest priority criteria for subcontractor selection, with the most influential sub-criteria being quality work specifications, tender prices, and having an HSE supervisor on the project. Originality: Selection of the right Subcontractor is very important for the successful completion of the project and the continuity of the contractor's business as most of the construction project work is carried out by subcontractors. This research on subcontractor selection is to reduce errors in the selection of subcontractors in construction projects and to understand multi-criteria decision-making using the AHP and TOPSIS methods.